Smart Village Program Implementation In Hanura Village, Teluk Pandan District, Pesawaran District, Lampung Province - Lies Kumara Dewi; Ahmad Junaiedi; Eka Ubaya Taruna Rauf; Erwin Putubasai (IHSA Institute, 2022)
The Making Indonesia 4.0 Roadmap is Indonesia's strategy to improve the national industry so that it can compete in the global industry. To support the Making Indonesia 4.0 Roadmap, the Government issued Presidential Regulation Number 95 of 2018 concerning the Electronic-Based Government System which gave rise to the concepts of Smart Nation, Smart Province, Smart City, Smart Regency, and Smart Village. Smart village is a policy program that creates a village so that it is able and able to solve its own problems intelligently and villages that can and are able to use digital technology to develop potential at the village level for the welfare of its people. Based on the Lampung Governor's Decree Number G/228/II.02/HK/2020 of 2020 regarding the determination of the target location for the smart village pilot project in Lampung Province, Hanura Village was chosen to represent Pesawaran Regency in mid-September 2020. Social changes due to the existence of smart villages in the village Hanura includes elements in a smart village, namely smart government, smart community, smart economy, smart living, smart environment, and smart mobility. This means that the implementation of the smart village program in Hanura Village, Teluk Pandan District, Pesawaran Regency is quite good, but still needs to be improved so that the smart village program's objectives are as expected, namely improving the quality of community life and community welfare by utilizing information technology so that Hanura village becomes a developed village. and not left behind from other villages.